Life cycle environmental assessment of Refuse-Derived Fuel (RDF) as an alternative to fossil fuels in cement production: A sustainable approach for mitigating carbon emissions - Helia Salaripoor; Hossein Yousefi; Mahmood Abdoos (Fuel Communications)
This study evaluates the environmental impacts of using Refuse-Derived Fuel (RDF) as an alternative fuel in the cement industry during natural gas shortages in Tehran, Iran. Given the increasing municipal solid waste production and the cement industry's significant carbon emissions, this research takes an innovative approach to assess RDF's potential to mitigate these issues through a life cycle approach. The analysis employs OpenLCA software to compare the environmental effects of RDF against traditional fossil fuels fuel oil and coal during colder months when natural gas is scarce. The study examines two RDF compositions, including organic waste and one excluding it, to determine their impacts on sustainability and fuel efficiency. Key findings indicate that RDF, mainly when produced with organic waste, offers substantial reductions in global warming potential (GWP) and other environmental impacts compared to conventional fuels. Specifically, the results demonstrate that RDF can significantly lower CO₂ emissions associated with cement production, positioning it as a viable option for enhancing energy sustainability within the industry. This research underscores the importance of integrating waste management strategies with energy recovery solutions, providing valuable insights for policymakers aiming to address both waste disposal and energy needs sustainably.